Sistem Pendukung Keputusan Dalam Pemilihan Peserta Beasiswa Magister Menggunakan Metode SAW - Neni Mulyani; Jeperson Hutahaean; Zulfi Azhar; Aulia Kartika (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
A scholarship is a gift given by the government or a university to help reduce the cost of education where the higher the level of education taken, the more money that must be provided to fulfill, the opportunity to be able to continue master's education is the dream of many young scholars. Every opportunity that is open to get a master's scholarship makes many prospective scholarship recipients compete to register themselves as participants, but not all participants who apply to receive scholarships get the same opportunity because the quota is limited. It is necessary to make a selection in determining the award of scholarships to the right people and avoid fraud in the selection process, this can be solved by using the application of computer science, namely a decision support system assisted by applying the SAW method in obtaining more systematic results based on previous research. the results obtained in this study